ASSESSMENT OF TECHNOLOGY COMPETITIVENESS ABILITIES IN INDONESIAN WAR SHIP IN ASIA - Harun Bekti Ariyoko; I Nengah Putra; Okol Sri Suharyo (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2019)
The assessment of technological competitiveness can be carried out at the level of a stage of transformation on a warship. With the dynamics of defence and security threats to the Indonesian state, both symmetrical and asymmetrical, warship technology must continue to improve combat capability and professionalism of human resources in accordance with technological developments towards the industrial revolution 4.0, in order to have a high level of competitiveness. The purpose of this study is to determine the strengths and weaknesses of warship performance through the assessment of technological capabilities. The research result, at the level of technological capability and the existing gap of fourth components, where the current level of capability on warships W has a gap of the technological development that is farthest away with countries Y and Z is the development of the level of technological capability on technical devices and followed by developments the level of technological capability in human resources (soldiers). The benefits of the research are expected to be used as material for consideration by planners and decision makers in integrating technological considerations into the planning of warship development in the modern era.Keywords: Technology Capability Assessment, Warship Technology, Techometrics